Evolution of the Second-Phase Particles and Their Effect on Tensile Fracture Behavior of 2219 Al-xCu Alloys - Daofen Xu; Kanghua Chen; Yunqiang Chen; Songyi Chen (Metals, 2020)
In this study, the continuous evolution of the second-phase particles across as-cast, homogenization, multi-directional forging (MDF), and solution-aging treatment and their effect on tensile fracture behavior of 2219 aluminum alloys with different Cu contents was examined by optical microscopy (OM), scanning electron microscopy (SEM), and tensile tests. The results showed that the microstructure of as-cast 2219 aluminum alloy consisted of the α-Al matrix, Al2Cu coarse phase, and Fe-rich impurity phase. Severe segregation of Cu existed, and eutectic networks can be observed in the ingot. With an increase in Cu content, the eutectic networks became coarsen and thicker. During the complex improved process, the refinement mechanisms were fragmentation, dissolution, and diffusion of Al2Cu particles. Most fine Al2Cu particles were fully dissolved into the matrix and partial coarse particles were still retained after solution-aging treatment. Thus, the elongations of all the samples, undergoing solution treatment followed by water quenching, increased evidently. Then, the elongations decreased slightly due to the increase of precipitates. The fractography analysis of peak aged condition samples indicated that the fracture mode was diverted from a typical inter-granular fracture to a mainly trans-granular fracture with increase in Cu content from 5.56% to 6.52%. Fracture initiation mainly occurred by original microcrack propagation and microvoid nucleation at the coarse constituents.